Analytical weight optimization of an enclosed stressed skin derrick - Balkhi, Abdullah; Azimifar, Ali (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2013)
The demand for drilling operations in Arctic regions is growing significantly due to an increasing need for oil and gas. The harsh environment in Arctic regions requires safe and acceptable working conditions. In order to still have an acceptable working environment and protection for drilling and pipe handling equipment, it is important to make improvements in design of upcoming drilling rigs. One of the items that needed to be developed is the derrick/drill tower, which today is mainly constructed as a structural framework and has limited working areas where crews can work without exposure to the weather and winds. A low structural weight of a derrick is desired in order to achieve improved and sustained stability conditions. The objectives with the present study is to propose a weight-optimized stressed skin derrick and compare the design with a covered conventional truss derrick with respect to weight and strength. Aker MH has provided data about a conventional truss derrick which was used as a reference derrick for input of loads, dimensions and weights in order to design a new derrick. To ensure enough structural strength against yielding and buckling, structural analyses were carried out by using a finite element analysis based on 3D beam theory. Numerical optimization of outer plating thickness, stiffeners and stringer dimensions were performed by using the numerical computation software Matlab. After the optimization against buckling and yielding, a final weight of 465 mT was achieved. This weight can be compared to a covered conventional truss derrick which is estimated to 590 mT. The reduction of weight is 21 % compared to a covered conventional truss derrick. The vertical centre of gravity of the new derrick design was reduced by 1.5 m. By introducing radius in the corner of a stressed skin derrick, the wind forces acting on the derrick were decreased significantly and this provides sustained stability for a drilling unit. Due to lower weight in the new design, the manufacturing costs were reduced by ...